Improving sonographic visualisation of the appendix in a regional referral hospital - Shyr Chui; Carly Phinney; Karina Hansen; Deanna Danskin (BMJ Open Quality)
Ultrasound is a first-line and often preferred imaging modality in the diagnosis of acute appendicitis. When the appendix is not visualised during a dedicated appendix ultrasound study, patients may require a CT study, which uses ionising radiation, or undergo conservative clinical observation with the inherent risk of clinical deterioration, perforation and sepsis. Median baseline data, at our hospital imaging department, revealed a rate of combined normal and abnormal appendix visualisation of 34.5% which is below the reported visualisation rates in the North American literature and well below the rates reported in the global literature. We embarked on a formal quality improvement (QI) project to improve the rates of appendix visualisation in our hospital ultrasound department. Using the Model of Improvement framework and a team approach, we generated and trialled multiple plan-do-study-act interventions over a project term of 12 months. In the second half of the project term, we saw a sustained rise in appendix visualisation exceeding our original stretch goal of 75% visualisation which was sustained 6 months after the formal project end (p<0.001). This rise was accompanied by a commensurate increase in sonographer confidence in appendix visualisation. In our case, the Model of Improvement methodology proved successful in solving our complex problem of sonographic appendix under-visualisation. The learnings of this QI project have been widely shared and spread according to the ethos of QI.